VD_FINDINFO Faillite / 2019 / 30 vom 1. November 2019 - VD Tribunal cantonal (2019)
FAILLITE SANS POURSUITE PRÉALABLE, SUSPENSION DE LA PROCÉDURE, CRÉANCIER, INSOLVABILITÉ | 190 al. 1 ch. 2 LP, 207 al. 1 LP, 207 LP